Diabetes and Host Resistance I. Effect of Alloxan Diabetes Upon the Phagocytic and Bactericidal Efficiency of Rat Leukocytes for Pneumococcus - Briscoe, H. Frances (1965)
Briscoe, H. Frances (University Medical Center, Jackson, Miss.), and Fred Allison, Jr. Diabetes and host resistance. I. Effect of alloxan diabetes upon the phagocytic and bactericidal efficiency of rat leukocytes for pneumococcus. J. Bacteriol. 90:1537–1541. 1965.—Chronic diabetes mellitus was induced in rats with alloxan monohydrate. Glycosuria persisted for the 6 weeks of study, but ketonuria was never encountered. The cellular composition of peritoneal exudate recovered from diabetic rats after starch aleuronat administration was the same as that obtained from normal rats. The quantity of exudate recovered from the diabetic rats was thought to be less than that obtained from normal rats subjected to the same irritant. Phagocytosis was found to be essentially the same for both diabetic and normal cells when suspended in normal saline. The killing efficiency of harvested peritoneal phagocytes suspended in saline from both diabetic and normal rats for type 1 pneumococcus was compared and no difference between the groups was found.